Rove Beetles of Florida, Staphylinidae (Insecta: Coleoptera: Staphylinidae) - John Howard Frank; Michael C. Thomas (EDIS, 2002)
This document is EENY-115 (originally published as DPI Entomology Circular No. 343), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 1999. Revised: December 2002.